The discriminant analysis of agroecological influence of ways of machining of soil - Цьова, Ю. А. (Scientific Progress & Innovations, 2016)
The article presents the results of discriminant analysis on the state of soil on edaphic parameters of the system, which are formed as a result of different methods of machining. Two initial discriminant axes is enough for discrimination of results of chisel cultivation, subsurface cultivation, minimum tillage, and also «no till». Canonical axes 1 discriminates ways of machining with high depth of ploughing and ways with small depth or zero processing. Canonical axes 2 discriminates each of the first groups on subgroups with smaller depth of ploughing in each pair. Deeper variants of a ploughed land differ by the big levels of nutrients (nitrogen, phosphorus, potassium) in soil. Values of canonical variables are considered as markers of axes of space in which limits variability of edaphic indicators is reflected.